Building A Madani Person (Becoming Independent, Creative and Innovative) at LKSA Muhammadiyah Nanggulan Orphanage, Kulon Progo - Zahro Varisna Rohmadani; Andhita Dyorita Khoiryasdien (CV. Doki Course and Training, 2025)
The purpose of this PKM program is to help partners overcome existing problems in the form of financial and mental problems. The problems experienced by partners are (1) mental health, difficult conditions make partner children feel less confident in their potential, and confused about their future, (2) economic independence, partners still depend on donations given by donors in meeting their daily needs. The solution provided is to empower the community by: (1) education related to character education, (2) education related to fostering interest in entrepreneurship from an early age, (3) education related to financial management for children; so as to achieve an independent, creative and innovative person. The results obtained from this program are: partners show high motivation to compete; have the ability to make decisions and deal with problems that arise; have a strong sense of confidence and responsibility; realize the importance of creating jobs and how to develop an entrepreneurial spirit from an early age; partners also have an understanding of how to keep simple records and save money to live fruitfully.